Land use and cover changes in the Mampong Municipality of the Ashanti Region - Frimpong, Bernard Fosu (2016)
A thesis submitted to the Department of Theoretical and Applied Biology, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science in Environmental Science, 2015